Patient self-management and pharmacist-led patient self-management in Hong Kong: A focus group study from different healthcare professionals' perspectives - Wong Eliza LY; You Joyce HS; Chan Frank WK; Wong Fiona YY; Yeoh EK (BMC Health Services Research, 2011)
Abstract Background Patient self-management is a key approach to manage non-communicable diseases. A pharmacist-led approach in patient self-management means collaborative care between pharmacists and patients. However, the development of both patient self-management and role of pharmacists is limited in Hong Kong. The objectives of this study are to understand the perspectives of physicians, pharmacists, traditional Chinese medicine (TCM) practitioners, and dispensers on self-management of patients with chronic conditions, in addition to exploring the possibilities of developing pharmacist-led patient self-management in Hong Kong. Methods Participants were invited through the University as well as professional networks. Fifty-one participants comprised of physicians, pharmacists, TCM practitioners and dispensers participated in homogenous focus group discussions. Perspectives in patient self-management and pharmacist-led patient self-management were discussed. The discussions were audio recorded, transcribed and analysed accordingly. Results The majority of the participants were in support of patients with stable chronic diseases engaging in self-management. Medication compliance, monitoring of disease parameters and complications, lifestyle modification and identifying situations to seek help from health professionals were generally agreed to be covered in patient self-management. All pharmacists believed that they had extended roles in addition to drug management but the other three professionals believed that pharmacists were drug experts only and could only play an assisting role. Physicians, TCM practitioners, and dispensers were concerned that pharmacist-led patient self-management could be hindered, due to unfamiliarity with the pharmacy profession, the perception of insufficient training in disease management, and lack of trust of patients. Conclusions An effective chronic disease management model should involve patients in stable condition to participate in self-management in order to prevent health deterioration and to save healthcare costs. The role of pharmacists should not be limited to drugs and should be extended in the primary healthcare system. Pharmacist-led patient self-management could be developed gradually with the support of government by enhancing pharmacists' responsibilities in health services and developing public-private partnership with community pharmacists. Developing facilitating measures to enhance the implementation of the pharmacist-led approach should also be considered, such as allowing pharmacists to access electronic health records, as well as deregulation of more prescription-only medicines to pharmacy-only medicines.